Development of an enzyme-linked immunosorbent assay and a dipstick assay for the rapid analysis of trans-resveratrol in grape berries. (1st September 2019) - Chen, Xiaojiao; He, Junhu; Tan, Guiyu; Liang, Ju; Hou, Yuxia; Wang, Mian; Wang, Baomin
Highlights: The mAb3C9 against trans -resveratrol with a new hapten was sensitive and specific. Using mAb 3C9, we developed icELISA and LFIA for trans -resveratrol analysis. To identify trans -resveratrol levels in grapes, they can be screened by LFIA. Abstract: trans -Resveratrol, a natural polyphenol present in grapes, has many beneficial effects to human health. However, measurement of trans -resveratrol is technically complicated and time-consuming. In the present study, we obtained a sensitive and specific monoclonal antibody (mAb), namely 3C9, against trans -resveratrol. An indirect competitive enzyme-linked immunosorbent assay (icELISA) was developed, with 50% inhibitory concentration and working range of 1.0 ng/mL and 0.19–4.9 ng/mL, respectively. A lateral flow immunoassay (LFIA) based on 3C9 was also developed for the semiquantitative detection of trans -resveratrol in an indicator range of 50–100 ng/mL. Average recoveries of trans -resveratrol spiked in red and green grape berries samples were respectively 88–107% and 83–102% by icELISA. The icELISA and LFIA were applied for determination of trans -resveratrol in grape berries. The results were highly consistent with those determined by high-performance liquid chromatography analysis (R 2  = 0.9997). Therefore, we conclude that the immunoassay methods are suitable for the large-scale screening of trans -resveratrol in grape quality breeding.